Liver resection for single large hepatocellular carcinoma: a prognostic factors study - Vincent Nguyen-Khac; Raffaele Brustia; Rami Rhaiem; Hélène Regnault; Anna Sessa; Sebastien Mule; Christophe Duvoux; Alexis Laurent; Vincent Leroy; Julien Calderaro; Alain Luciani; Francoise Roudot-Thoraval; et al. (Annals of Hepatology, 2022)
Introduction and objectives: Liver resection is the only curative therapeutic option for large hepatocellular carcinoma (> 5 cm), but survival is worse than in smaller tumours, mostly due to the high recurrence rate. There is currently no proper tool for stratifying relapse risk. Herein, we investigated prognostic factors before hepatectomy in patients with a single large hepatocellular carcinoma (HCC). Material and methods: We retrospectively identified 119 patients who underwent liver resection for a single large HCC in 2 tertiary academic French centres and collected pre- and post-operative clinical, biological and radiological features. The primary outcome was overall survival at five years. Secondary outcomes were recurrence-free survival at five years and prognostic factors for recurrence. Results: A total of 84% of the patients were male, and the median age was 66 years old (IQR 58–74). Thirty-nine (33%) had Child–Pugh A cirrhosis, and the mean Model for End-Stage Liver Disease (MELD) score was 6 (6–6). The aetiology of liver disease was predominantly alcohol-related (48%), followed by nonalcoholic steatohepatitis (22%), hepatitis B (18%) and hepatitis C (10%). The mean tumour size was 70 mm (55–110). The median overall survival was 72.5 months (IC 95%: 56.2-88.7), and the five-year overall survival was 55.1 ± 5.5%. The median recurrence-free survival was 26.6 months (95% CI: 16.0-37.1), and the five-year recurrence-free survival rate was 37.8 ± 5%. In multivariate analysis, preoperative prognostic factors for recurrence were baseline alpha-fetoprotein (AFP) > 7 ng/mL (p<0.001), portal veinous invasion (p=0.003) and cirrhosis (p=0.020). Using these factors, we created a simple recurrence-risk scoring system that classified three groups with distinct disease-free survival medians (p<0.001): no risk factors (65 months), 1 risk factor (36 months), and ≥2 risk factors (8.9 months). Conclusion: Liver resection is the only curative option for large HCC, and we confirmed that survival could be acceptable in experienced centres. Recurrence is the primary issue of surgery, and we proposed a simple preoperative score to help identify patients with the most worrisome prognosis and possible candidates for combined therapy.